Coporate Sosial Responsibility ''CSR Beyond Borders'' Colours Of Life at Arked Niaga Padang Besar Perlis - Jamali; Desti Umita Sari Sikumbang (PASAI : Jurnal Pengabdian kepada Masyarakat, 2024)
The international community service program "CSR Beyond Borders – Colours of Life" was conducted at Arked Niaga Padang Besar, Perlis, through a collaboration between the Forum Komunikasi Perguruan Tinggi (FKPT) of Aceh and North Sumatra and educational institutions from Malaysia and Thailand. The program aimed to empower local micro and small enterprises (MSEs) by enhancing entrepreneurial skills, promoting cultural heritage, and fostering cross-border collaborations. Additionally, it sought to raise awareness about corporate social responsibility (CSR) and environmental sustainability among community members. The program employed a participatory and collaborative approach. Initial stages involved field observations and needs assessments to identify local potentials and challenges. Subsequently, educational sessions on CSR, cultural preservation, and sustainable entrepreneurship practices were conducted. Workshops and practical training sessions were organized to enhance skills in local product development, digital marketing strategies, and financial management for small businesses. Continuous mentoring was provided to ensure the application of acquired knowledge and skills, accompanied by regular evaluations to monitor progress. Through FKPT's involvement, the program strengthened inter-university collaborations and expanded its impact via knowledge and resource exchange. The outcomes indicated significant improvements in MSE capacities, preservation of local cultural heritage, and the establishment of sustainable cross-border collaborations. This program serves as an effective model for cross-border community service initiatives, fostering social and economic development in border regions.